(untitled) (Intent Research Scientific Journal, 2025)
This study aims to improve the methodology for forming a positive mood in relation to cognitive activity on the example of preschool students. The study analyzes effective pedagogical approaches that serve to improve the motivation, interest and emotional state of students in the process of teaching them. It also examines psychological and didactic methods aimed at increasing students’ cognitive activity, developing independent thinking and problem-solving skills. The results of the study provide teachers with recommendations for creating a favorable learning environment for students and promoting their professional development.